2023
DOI: 10.2147/ijgm.s406466
|View full text |Cite
|
Sign up to set email alerts
|

Does Biological Sex Matter in Lyme Disease? The Need for Sex-Disaggregated Data in Persistent Illness

Abstract: Background Biological sex should be included as an important variable in clinical research studies to identify outcome differences between men and women. Very few Lyme disease studies were designed to consider sex-based differences or gender bias as an important component of the research design. Methods To assess sex-based differences in Lyme disease patients who were clinically diagnosed and reported remaining ill for six or more months after receiving antibiotic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Among those who did not go into full remission, 60% of women (3/5) and 53.3% of men (8/15) also improved by 30% or greater, with 2 women and 2 men both having improvements ranging from 5–15%. In a recent study by Johnson et al, using self-reported clinical data from 2170 patients in the MyLymeData patient registry [ 157 ], the authors found no differences in antibiotic treatment response or side effects between women and men. We found similar results and agree that biological sex should be integrated into Lyme disease research as a distinct variable since male and female hormones can be affected by Borrelia burgdorferi [ 50 , 158 , 159 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among those who did not go into full remission, 60% of women (3/5) and 53.3% of men (8/15) also improved by 30% or greater, with 2 women and 2 men both having improvements ranging from 5–15%. In a recent study by Johnson et al, using self-reported clinical data from 2170 patients in the MyLymeData patient registry [ 157 ], the authors found no differences in antibiotic treatment response or side effects between women and men. We found similar results and agree that biological sex should be integrated into Lyme disease research as a distinct variable since male and female hormones can be affected by Borrelia burgdorferi [ 50 , 158 , 159 ].…”
Section: Resultsmentioning
confidence: 99%